New L-stable modified trapezoidal methods for the initial value problems - Yaakub, Abdul Razak; Evans, D. J. (Taylor & Francis, 2003)
New L-stable trapezoidal formulas obtained by modifying the nonlinear trapezoidal formulas are presented. Numerical results are presented to confirm the theoretical stability analysis.